Pengaruh Model Pembelajaran Write Around Terhadap Kemampuan Mengalihwahanakan Teks Negosiasi ke Bentuk Naratif Siswa Fase E SMA Negeri 3 Pariaman - Rachmadona Utami Dona (Signifiѐ, 2023)
This research is motivated by problems, namely students find it difficult to develop ideas, ideas, creativity in writing negotiation texts into narrative form,, students do not understand the material to convert negotiation texts to narrative forms delivered Teachers, students still have many mistakes in writing negotiation texts into narrative form. This study aims to describe, whichaffects the use of the Write Around learning model on the ability to translate negotiation texts into narrative form for phase E students of SMA Negeri 3 Pariaman. This type of research is quantitative research using Pre-experimental methods. The design of this study is One Group Pretest-Posttest Desaign. The sample of this study was phase XE.1 students of SMA Negeri 3 Pariaman totaling 36 students. The data was analyzed and then a t-test was carried out to determine the effect of the Write Around learning model on the ability to translate negotiation texts into narrative form for phase E students. This research data is a worksheet of the ability to write narrative texts for phase E students of SMA Negeri 3 Pariaman before and after the use of the Write Around learning model. This study can be summed up as follows. First, the ability to translate negotiation texts into narrative form for phase E students before using the Write Around learning model obtained an average score of 65.74 in the range of 56-65% with qualifications that are sufficient (C). Second, the ability to translate negotiation texts into narrative form for phase E students after using the Write Around learning model obtained an average score of 76.38 in the range of 76-85% with good qualifications (B). Third, there is a significant influence on the use of the Write Around learning model on the ability to translate negotiation texts into narrative form for phase E students of SMA Negeri 3 Pariaman because tcount>ttable (4.05 >1.66).